Civilian casualty inequity, partisanship, and American public support for Israel. Issue 2 (3rd May 2016) - Leep, Matthew; Coen, Alise
Abstract : Research into how civilian casualties influence public opinion largely focuses on citizens' support for the use of force by their own countries. This study explores how civilian casualties and partisan cues shape support for the use of force by an ally in a foreign conflict. Specifically, it assesses the effects of civilian casualty inequity – the uneven distribution of civilian casualties across two sides in a conflict – on Americans' support for Israel. Drawing on an original survey experiment conducted during the 2014 Israel–Gaza conflict, the article bridges work on inequity aversion theory, party identification, and social identity theory. It finds that civilian casualty inequity information reduces support for Israel, particularly among Independents. The study also finds that adding explicit partisan criticism cues to civilian casualty inequity information does not appear to induce motivated evaluations of Israel among Republicans or Democrats. An important implication is that under conditions of greater media coverage of civilian casualty inequity, Americans – particularly Independents – might become less supportive of Israel even in the absence of elite criticism of Israel.